Ṭur ‘Abdi̇n’de üçlü yerleşi̇m modeli̇: manastir, köy, Kayaya Oyma Manastir - Keser, Elif (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Ṭur ‘Abdin, located in south-eastern Turkey, is historically considered the homeland of the Syrian Orthodox community and regarded holy by the members of the community all over the world. This high plateau is remarkable for the significant number of villages and monasteries built mostly in the late antique and medieval periods. These settlements are located in close proximity. In the past, a pattern, namely ‘village and its satellite monastery or monasteries’ was identified about their physical relations. This short article takes it one step further by pointing out a model that features in several cases, namely the tripartite arrangement of village, monastery and rock-carved monastery. This paper gives four examples for the model.